PENYEBAB KEJADIAN PENDARAHAN PADA KEHAMILAN - Marfuaturohmah, Titin; Ayuningtyas, Ika Fitria (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Yogyakarta provincial department of health reported that maternal mortality reached 87.3 per100,000 live births in 2012, while the health profile of Sleman in 2012 revealed 87.6 maternal deaths per100,000 live births. Reports of provincial health department in 2012 showed that the cause of maternal deathin Indonesia was still dominated by bleeding (32%). Objective: To investigate the etiologies of bleeding in pregnancy. Methods: This study was descriptive and employed documentation study which evaluated the records at Sleman Hospital during the year of 2013. Research involved with 135 documentation samples. Results: The etiologies of bleeding in pregnancy at Sleman Hospital were abortion in 121 women (89.6%), placenta previa in 6 women (4.4%), interrupted ectopic pregnancy and mola hidatidosa pregnancy each was in 3 women (2.2%) and the least frequent was solusio placenta in 2 women (1.5%). Conclusion: Abortion was the most frequent etiology of bleeding in pregnancy (89.6%) at Sleman Hospital in 2013. Keywords: bleeding and pregnancy